2017
DOI: 10.1089/neu.2016.4778
|View full text |Cite
|
Sign up to set email alerts
|

Pain Input Impairs Recovery after Spinal Cord Injury: Treatment with Lidocaine

Abstract: More than 90% of spinal cord injuries are caused by traumatic accidents and are often associated with other tissue damage (polytrauma) that can provide a source of continued pain input during recovery. In a clinically relevant spinal cord contusion injury model, prior work has shown that noxious stimulation at an intensity that engages pain (C) fibers soon after injury augments secondary injury and impairs functional recovery. Noxious input increases the expression of pro-inflammatory cytokines (interleukin 1β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Recent work suggests that this process is related to the breakdown of the blood spinal cord barrier (BSCB). Supporting this, Turtle et al ( 2017 ) showed that the application of shock or capsaicin a day after rats received a contusion injury increased the infiltration of red blood cells into the injured tissue. Because hemoglobin is cytotoxic (Regan and Guo, 1998 ), this would fuel cell death and the expansion of injury.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recent work suggests that this process is related to the breakdown of the blood spinal cord barrier (BSCB). Supporting this, Turtle et al ( 2017 ) showed that the application of shock or capsaicin a day after rats received a contusion injury increased the infiltration of red blood cells into the injured tissue. Because hemoglobin is cytotoxic (Regan and Guo, 1998 ), this would fuel cell death and the expansion of injury.…”
Section: Discussionmentioning
confidence: 91%
“…This conclusion is based on work examining the effect of systemic morphine, given at a dose that completely blocks both spinal and brain-dependent responses to nociceptive stimulation (Hook et al, 2007 ). Morphine had no effect on shock-induced hemorrhage (Turtle et al, 2017 ). Nor did it attenuate the effect of shock treatment on long-term recovery (Hook et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine, which was the first sodium (Na + ) channel blocker, is still widely used in clinic as an amide-type local anesthetic agent now. 1 It inhibits nerve impulse transmission by blocking the fast voltage-gated Na + channels in the neuronal cell membrane thereby producing local anesthetic action. Lidocaine has good activity when it is applied to superficial body sites, penetrating mucous membranes to reduce the sensation of pain.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently Hook et al, found that administration of morphine, an opioid receptor agonist resulted in reduced sensory and motor recovery after SCI [306][307][308]. In the intact CNS the effect of transmission of impulses from nociceptive afferents is under the control of supraspinal systems originating in the midbrain (periaqueductal grey), and medulla (reticularis gigantocellularis (RG) and nucleus raphe magnus, (NRM)) [309].…”
Section: Future Directions 1: Deciphering Physiological Mechanismsmentioning
confidence: 99%